Product Promotion, Price, and Quality Analysis on Consumer Buying Interest In CV Kenli Chemical Jaya - Erika Ramadani; Husni Ritonga (Penerbit Jurnal Indonesia, 2025)
Buying interest refers to an individual's likelihood of acquiring a particular product and is also an important aspect in assessing consumer behavior. This study aims to analyze the influence of promotion, price, and product quality on consumer buying interest in CV Kenli Chemical Jaya. The research uses a quantitative approach with a survey method. The population in this study is all consumers of CV Kenli Chemical Jaya which totals 1,645 people. Sampling was done using the purposive sampling technique with the Slovin formula so that a sample of 94 respondents was obtained. The data collection technique was carried out through the distribution of questionnaires on the Likert scale, observation, and documentation. The collected data was analyzed using multiple linear regression analysis techniques with the help of SPSS software. The results of the study show that simultaneously promotion, price, and product quality significantly affect consumer buying interest. Partially, promotion and price have no influence on buying interest, while product quality shows a positive and significant relationship with buying interest. The coefficient of determination (R²) obtained in this study is 00.317, which means that 31.7% of the variables of consumer buying interest can be explained by the variables of promotion, price, and product quality. Meanwhile, the remaining 68.3% was influenced by other factors that were not studied in this study.